PENGARUH ORIENTASI PASAR, INOVASI PRODUK, DAN STRATEGIS KREATIVITAS PEMASARAN TERHADAP KINERJA PEMASARAN PADA UMKM KERAJINAN KOPIAH RESAM DESA DENDANG KECAMATAN KELAPA BANGKA BARAT - Siti Napisah; Selindia Selindia (LPPM STIE PERTIBA Pangkalpinang, 2022)
The purpose of this study was to determine the effect of market oriented, product innovation and strategic marketing creativity on Kopiah Resam in Dendang Village, Kelapa Bangka Barat. The sample in this study amounted to 187 people us Dusun Belit, Dusun Juruh and Dusun Ganjan using the Slovin method. The data analysis in this study is quantitative using multiple linear regression methods and the data is analyzed using the SPSS 25 program. Simultaneously independent variables (market orientation, product innovation and strategic marketing creativity) have a significant effect on the dependent variable (Marketing Performance) in the Kopiah Resam MSME. R Square value of 0.535 or 53.5% means that the Purchase Decision variable in the Marketing Performance Study of in Dendang Village, Kelapa Bangka Barat is influenced by marketing orientation, product innovation and strategic creativity while the remaining 46.5% is influenced by other variables not used in this study.